Reducing the Turbidity Level of Bengawan River Water in Solo Using the Jar Test Method with Al2(SO4)3 and Ca(OH)2 Coagulants - Adela Kayisi, Layung; Rendy Dwi Yulianto, Achmad; Mahardika Putri, Sekar; Sulistiyo Nugroho, Budi (Advances In Social Humanities Research, 2024)
Water is a compound composed of hydrogen (H?) and oxygen (O?), with turbidity caused by suspended particles such as clay and sewage. This study aims to reduce the turbidity of the Bengawan Solo River using the jar test method with pre-sedimentation and no pre-sedimentation treatment. The results showed that pre-sedimentation decreased the mean turbidity from 55.08 NTU to 30.16 NTU. The primary coagulant Al?(SO?)? and the auxiliary coagulant Ca(OH)? affect the turbidity and pH of the water. The pH value was close to neutral (6.07) achieved at a concentration of 60 ppm with pre-sedimentation. This method is effective in reducing turbidity and has the potential to be applied in large-scale water treatment.